2003
DOI: 10.1029/2002jd002741
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale study of a thick stratospheric ozone lamina at the edge of the southern subtropical barrier

Abstract: [1] A large-scale transport event resulting in a thick ozone lamina originating from midlatitudes is observed in the tropical stratosphere over Reunion island (55°E, 21°S). This isentropic transport was detected from stratospheric balloon-borne ozone measurements that showed the occurrence of the lamina and was investigated using different tools based on Ertel's potential vorticity (Epv) analyses. An original software (DYBAL) using surface coordinate and the equivalent length of Epv contours as diagnostic tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 41 publications
3
54
0
Order By: Relevance
“…7 that the variability in TOC monthly anomaly over SSO is in quasi-anti-phase with the QBO modulation, and the amplitude of TOC anomaly is in the 6 DU range and in accordance with the above explanation. These results are consistent with those found in other midlatitude regions as observed in global satellite data (Randel and Wu, 1996;Yang and Tung, 1994;Baldwin, 2001) or in individual station as over the Tibetan Plateau (Zou et al, 2000) and over Lauder on New Zealand (Brinksma et al, 1998).…”
Section: Interannual Toc Variabilitysupporting
confidence: 81%
See 2 more Smart Citations
“…7 that the variability in TOC monthly anomaly over SSO is in quasi-anti-phase with the QBO modulation, and the amplitude of TOC anomaly is in the 6 DU range and in accordance with the above explanation. These results are consistent with those found in other midlatitude regions as observed in global satellite data (Randel and Wu, 1996;Yang and Tung, 1994;Baldwin, 2001) or in individual station as over the Tibetan Plateau (Zou et al, 2000) and over Lauder on New Zealand (Brinksma et al, 1998).…”
Section: Interannual Toc Variabilitysupporting
confidence: 81%
“…These results are in accordance with results obtained by Rigozo et al (2012) in a local reconstructed daily ozone time series over the south of Brazil. In other midlatitude regions, similar results were observed in SAGE II data by singular value decomposition (Randel and Wu, 1996;Fioletov at al., 2006), TOMS data by Yang and Tung (1994), MLS satellite ozone profile by wavelets analyses (Fadnavis and Beig, 2008). In addition, numerical studies in general circulation models (Chipperfield et al, 1994;Takahashi, 1999) found the ozone anomaly in midlatitude regions in approximately opposite phase in comparison with the QBO index.…”
Section: Interannual Toc Variabilitysupporting
confidence: 74%
See 1 more Smart Citation
“…The MIMOSA model can also be used to determine the origin of air masses influencing a given site, similar to an isentropic Lagrangian trajectory model. The MIMOSA model is frequently used to detect the origin of air masses inducing laminae on ozone profiles Portafaix et al, 2003).…”
Section: Mimosa Modelmentioning
confidence: 99%
“…As reported by Russell et al (1996), in addition to the prodigious increase in the stratospheric aerosol loading, this event significantly affected numerous aspects of the atmospheric system, including (i) a 2-year cooling of the global surface temperature of several tens of degrees (Canty et al, 2013;Wunderlich and Mitchell, 2017), (ii) a warming of the tropical stratosphere ranging from 1 to 4 • C (Labitzke and McCormick et al, 1992;Young et al, 1994), and (iii) a lifting of the tropical ozone layer by ∼ 1.8 km (Pueschel et al, 1992;Grant et al, 1994). Through the use of satellite and balloon-borne observations, various studies have shown that moderate volcanic eruptions (i.e., volcanic explosive index less than or equal to 4) can significantly modulate stratospheric aerosol concentrations Kravitz et al, 2010;Solomon et al, 2011;Vernier et al, 2011;Clarisse et al, 2012;Jégou et al, 2013).…”
mentioning
confidence: 99%